Chemical constituents from the soft coral Sinularia digitata. Issue 5 (25th October 2019) - Huong, Nguyen Thi; Ngoc, Ninh Thi; Hanh, Tran Thi Hong; Quang, Tran Hong; Cuong, Nguyen Xuan; Nam, Nguyen Hoai; Van Minh, Chau
Abstract: Using various chromatographic separations, six known compounds namely (1 R *, 2 E, 4 R *, 7 E, 10 S *, 11 S *, 12 R *)‐10, 18‐diacetoxy‐dolabella‐2, 7‐dien‐6‐one (1 ), emblide (2 ), sarcophine (3 ), (3 R )‐4‐[(2 R, 4 S )‐4‐acetoxy‐2‐hydoxy‐2, 6, 6‐trimethylcyclohexylidene‐3‐en‐2‐one (4 ), 3 β ‐hydroxypregna‐5, 16‐dien‐20‐one (5 ), and 3 β ‐hydroxyandrost‐5‐en‐17‐one (6 ) were isolated from a methanol extract of the Vietnamese soft coral Sinularia digitata . The structural elucidation was confirmed by extensive analysis of the 1D and 2D NMR spectroscopic data as well as comparison of them with the reported values.